Respons Lima Varietas Kubis (Brassica oleracea L.) Terhadap Serangan Hama Pemakan Daun Plutella Xylostella ( Lepidoptera ; Plutellidae) - Jerry. N Luhukay; Muhammad Riadh Uluputty; Ria Y Rumthe (Faculty of Agriculture, Pattimura University, 2013)
Efforts to increase crop production often faced difficulty with pests and diseases. The use of high yielding varieties can be an alternative control. This study aimed to determine the population and intensity of pest damage Plutella xylostella on five varieties of cabbage (Brassica oleraceae L.). The experiment was conducted in the village Waipirit in October 2012 until January 2013. The study was designed using a randomized block design with five treatments, namely cabbage as the Grand 11, KK-Cross, Green Coronet, Green Hero, and Investor. The results showed that Investors were varieties that were resistant to pests Plutella xylostella, indicated by low population groups such as eggs 2.75, 16.55 tails larvae and 1.95 tails pupae, and the low intensity of leaf damage 28.51% which was classified medium.